2017
DOI: 10.1136/bmjopen-2017-018186
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of inhaled corticosteroids in real life on clinical outcomes, sputum cells and systemic inflammation in asthmatics: a retrospective cohort study in a secondary care centre

Abstract: ObjectivesThe impact of inhaled corticosteroids (ICS) on eosinophilic inflammation in asthma is well established, but their effect in a real-life setting has not been extensively studied. Our purpose was to investigate the effect of ICS on airway and systemic inflammation as well as on clinical outcomes in patients with asthma from clinical practice.Design, setting and participantsWe conducted a retrospective analysis on asthmatics from a secondary care centre in whom ICS were initiated/increased (n=101), stop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 40 publications
1
34
0
1
Order By: Relevance
“…Airway eosinophilia is frequently observed in asthma but it is neither necessary nor sufficient for the development of the disease. However, the presence of eosinophils in sputum and blood can identify responders to inhaled or oral corticosteroids, [23][24][25] and they are an important marker in the management of asthma. The ICS users also had higher levels of eosinophils, and lower FEV 1 already at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Airway eosinophilia is frequently observed in asthma but it is neither necessary nor sufficient for the development of the disease. However, the presence of eosinophils in sputum and blood can identify responders to inhaled or oral corticosteroids, [23][24][25] and they are an important marker in the management of asthma. The ICS users also had higher levels of eosinophils, and lower FEV 1 already at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps surprisingly, the change in sputum eosinophils was not associated with lung function decline. This may be explained by the fact that it represents a phenotype shown to be responsive to increase ICS both in controlled clinical studies and in real life [42,43]. Therefore, sputum eosinophils are often associated with improvement in FEV 1 when change in ICS dosing is appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Having said that, it does not deny the clinical value of measuring T2 biomarkers in phenotyping asthma, once the diagnosis has been done [ 10 ]. Indeed, there is accumulating evidence that the response to inhaled corticosteroids is dependent on the type of airway inflammation, with both sputum eosinophils [ 10 , 11 ] and elevated F ENO [ 12 , 13 ] being predictive of good treatment responses. We previously showed that combining F ENO , blood eosinophils and IgE may help in identifying eosinophilic asthma in large and unselected populations with untreated and treated asthma [ 14 ].…”
mentioning
confidence: 99%